Nazwa marki produktu a komunikacja marketingowa - Smalec, Agnieszka (Brand Name and Marketing Communication, 2008)
One of symptoms of the increasing globalization is more frequent contacts with international markets. One of the key aspects of these contacts is the need to adapt business message to the needs and requirements of a given market, including the very important cultural differences. Marketing communication is the management of the company's dialogue with the market environment. It is to initiate and retain partner relations with market actors. If the market is not well researched, communication problems may occur. Understanding another culure is a very difficult task, as it involves giving up one's habits, customs and paradigms, in order to remain open to the requirements of the other party. In marketing communication appropriate means and forms of communication are important to amke it clear and understandable. One of the elements which may prove helpful for managers in overcoming cultural differences is the knowledge of behaviours in other cultures, of their markets. It should be remembered thet communiocation involves different sorts of noise, that is why preparing a message which is well adapted to the requirements of the particular market is so important.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 88-95